(untitled) (ЕтноАнтропоЗум, 2019)
Globally, the word „migration” is most often associated with long distances and moving from one country to another. In the shadow of this comprehension stands the phenomenon of contemporary internal migration. I present a more rarely analysed type of it—lifestyle migration of people who made the decision to quit living in the big city. From anthropological point of view, the study reveals push factors—the unfavourable matters about the civic area that one used to live in, and also pull factors that attract one to the new area. Placing them in the frame of counterurbanisation, I explore the close relations urban-rural migrants try to establish to both nature and small groups of society. Based on participant observation and interviews held with Polish lifestyle migrants and environmental activists, I point out the potential problems of the migrants in relation to the term “sustainability” which is central for their adjustments.